PERAN LEMBAGA PENDIDIKAN DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA - Ridwan Ridwan (Faculty of Law, Universitas Jenderal Soedirman, 2012)
Corruption act in Indonesia is a very serious crime and has serious consequences for the nation of Indonesia, and the most disadvantaged are the people, welfare of the people is the desire of every person difficult to realize, while eradication is very slow. Combating corruption is a very important part in saving the nation from the threat of destruction is therefore a serious effort is needed in its eradication. Educational institutions have an important role for the eradication of corruption in Indonesia, because of the higher education institutions by law forming the character of each person for anti-corruption can be done, for it's efforts to improve the science of divinity to be very important, so the morality of everyone, including law enforcement becomes an important part in real life can be maintained, the science of religion without science is incomplete. Key words: corruption, moral, education, divinity